The Famous Five (Five on a Hike Together) - Blyton, Enid; Eileen ,A. Soper (Great Britain Hodder and Stoughton, 1997)
Why does an escaped convict send a message to Dick in the dead of the night? And what can the strange message mean? The police refuse to help - so the Famous Five must find out for themselves ..